2019
DOI: 10.1155/2019/6028952
|View full text |Cite
|
Sign up to set email alerts
|

Association between Smoking and Liver Fibrosis among Patients with Nonalcoholic Fatty Liver Disease

Abstract: Objective We aimed at analyzing the role of smoking in hepatic fibrosis in patients with nonalcoholic fatty liver disease (NAFLD) and at exploring the related risk factors. Methods This was a cross-sectional study that included a total of 225 patients with NAFLD. Among them, 127 were nonsmokers and 98 were smokers. Liver significant fibrosis was diagnosed when the liver stiffness (LS) value was higher than 7.4 kPa. The diagnostic criterion for NAFLD was a controlled attenuation parameter (CAP) value of >238 dB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…19,43 Former and current cigarette smoking were associated with liver-related outcomes in line with previous findings that smoking is associated with liver fibrosis in those with NAFLD. 45 Liver enzymes were linked to liver-related outcomes suggesting that these enzymes may reflect disease activity and risk of disease progression. Similar associations have previously been reported especially with GGT.…”
Section: Risk Factors For Liver-related Outcomesmentioning
confidence: 99%
“…19,43 Former and current cigarette smoking were associated with liver-related outcomes in line with previous findings that smoking is associated with liver fibrosis in those with NAFLD. 45 Liver enzymes were linked to liver-related outcomes suggesting that these enzymes may reflect disease activity and risk of disease progression. Similar associations have previously been reported especially with GGT.…”
Section: Risk Factors For Liver-related Outcomesmentioning
confidence: 99%
“…Studies have shown the increased prevalence of cardiovascular disease (CVD) in patients with NAFLD, without and without diabetes [ 18 , 19 ]. Thus, NAFLD is generally associated with an unhealthy lifestyle, with evidence, to suggest that changes in unhealthy lifestyles can reduce the transaminase levels and improve NAFLD [ 20 ]. A study of patients with T2DM found a higher prevalence of peripheral vascular, coronary and cerebrovascular diseases in subjects with NAFLD than without, with coronary, cerebrovascular and peripheral vascular disease was greater among those with NAFLD than among those without this disease, aside from normal CVD risk factors, medication use and diabetes-related variables [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent study had reported that current smoking, pack‐years and urinary cotinine levels were associated with the risk of incident NAFLD 49 . Ou et al 50 analysed 225 NAFLD patients. NAFLD was diagnosed by TE.…”
Section: Discussionmentioning
confidence: 99%